Layperson mouth-to-mask ventilation using a modified I-gel laryngeal mask after brief onsite instruction: a manikin-based feasibility trial - Schälte, Gereon (BMJ Open, 2016)
OBJECTIVE: The intention of this manikin-based trial was to evaluate whether laypersons are able to operate an I-gel laryngeal mask (I-gel) modified for mouth-to-mask ventilation after receiving brief on-site instruction. SETTING: Entrance hall of a university hospital and the city campus of a public technical university, using a protected manikin scenario. METHODS: Laypersons were handed a labelled, mouthpiece-integrated I-gel laryngeal mask and a corresponding instruction chart and were asked to follow the printed instructions. OUTCOME MEASURES: The overall process was analysed and evaluated according to quality and duration. RESULTS: Data from 100 participants were analysed. Overall, 79% of participants were able to effectively ventilate the manikin, 90% placed the laryngeal mask with the correct turn and direction, 19% did not position the mask deep enough and 85% believed that their inhibition threshold for performing resuscitation was lowered. A significant reduction in reluctance before and after the trial was found (p<0.0001). A total of 35% of participants had concerns about applying first aid in an emergency. Former basic life support (BLS) training significantly reduced the time of insertion (19.6 s, 95% CI 17.8 to 21.5, p=0.0004) and increased overall success (p=0.0096). CONCLUSIONS: Laypersons were able to manage mouth-to-mask ventilation in the manikin with a reasonable success rate after receiving brief chart-based on-site instructions using a labelled I-gel mask. Positioning the mask deep enough and identifying whether the manikin was successfully ventilated were the main problems observed. A significant reduction in reluctance towards initialising BLS by using a modified supraglottic airway device (SAD) may lead to better acceptance of bystander resuscitation in laypersons, supporting the introduction of SADs into BLS courses and the stocking of SADs in units with public automatic external defibrillators.